2020
DOI: 10.3389/fimmu.2020.01046
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cytoplasmic Signaling of CD28ζ CARs for Improved Therapeutic Functions

Abstract: Chimeric antigen receptor modified T cells (CAR-T) have yielded impressive clinical outcomes in treating hematopoietic malignancies. However, relapses have occurred in a substantial number of patients and limited the development of CART therapy. Most underlying reasons for these relapses can be attributed to poor persistence and rapid exhaustion of CART cells in vivo. Despite multiple strategies having been developed, how to improve CART persistence or resist exhaustion while maintaining sufficient cytotoxic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…CD3ζ ITAMs have different roles in the regulation of T-cell activation; for example, mutations of CD3ζ ITAM1 and ITAM2 significantly impaired signal transduction and induced cell death. However, mutation of CD3ζ ITAM3 did not induce cell death, but rather increased IL-2 secretion and MAPK phosphorylation ( 99 , 100 ). CD28ζ-based CAR-T cells that only contain the ITAM1 domain resulted in higher percentages of T SCM and T CM and a lower fraction of T EFF cells and yielded long-lasting and complete tumor remission in an in vivo animal model ( Figure 4 ) ( 101 ).…”
Section: Strategies To Improve the Persistence Of Car-t Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…CD3ζ ITAMs have different roles in the regulation of T-cell activation; for example, mutations of CD3ζ ITAM1 and ITAM2 significantly impaired signal transduction and induced cell death. However, mutation of CD3ζ ITAM3 did not induce cell death, but rather increased IL-2 secretion and MAPK phosphorylation ( 99 , 100 ). CD28ζ-based CAR-T cells that only contain the ITAM1 domain resulted in higher percentages of T SCM and T CM and a lower fraction of T EFF cells and yielded long-lasting and complete tumor remission in an in vivo animal model ( Figure 4 ) ( 101 ).…”
Section: Strategies To Improve the Persistence Of Car-t Cellsmentioning
confidence: 98%
“…An ITAM domain consists of two consecutive YxxL/I motifs separated by a defined number of amino acids (YxxL/I-X6−8-YxxL/I) ( 98 ). TCR binding to the peptide–MHC complex leads to the activation of the Src family kinase Lck, which phosphorylates two tyrosine residues in each of the CD3ζ ITAMs ( 97 , 99 ). CD3ζ ITAMs have different roles in the regulation of T-cell activation; for example, mutations of CD3ζ ITAM1 and ITAM2 significantly impaired signal transduction and induced cell death.…”
Section: Strategies To Improve the Persistence Of Car-t Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the role of costimulatory signals in CAR-T development is well-established, the optimal costimulatory domains for CAR-T cells remains to be defined, and should be evaluated case-by-case in order to fine-tune immunotherapy approaches [37,38]. Literature reported that the choice of 4-1BB signaling domain in CARs conferred improved selectivity for higher tumor antigen density, reduced T cell exhaustion phenotype and reduced basal T-cell activation [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…20,[69][70][71][72] However, despite intensive research, the exact molecular mechanism of CAR-induced T cell activation is still not well understood. 73 It is known that signal transmission plays a key role in activation, but the mechanism of CAR signal transduction differs from that of the native TCR regarding its activation patters. 40,74 A side-by-side investigation using bulk and single-cell RNA sequencing showed distinct but similar transcriptional signatures between CD19-targeting CAR and TCR signaling.…”
Section: Signal Transduction and Strengthmentioning
confidence: 99%